The Book of Revelation: Plagues as Part of the Eschatological Human Condition. (September 2021) - Lietaert Peerbolte, Bert Jan
Although plagues and disease do not feature prominently in the book of Revelation, specific images from the book, including the four horsemen (Rev. 6) and bowls of wrath (Rev. 15–16), have been used in certain traditions in which epidemics and pandemics have been, and still are, being interpreted as part of the eschatological human condition: they are seen as inflicted on humanity, ultimately by an angry God, whose wrath will lead to a final judgment.